Дослідження умов формування потоку пульпи у пісковому жолобі односпірального класифікатора - Кондратець, Василь Олександрович; Мацуй, Анатолій Миколайович (НТУ "ХПІ", 2016)
Представлені результати дослідження формування і руху потоку пульпи у пісковому жолобі механічного односпірального класифікатора. При співударянні пісків і води у пісковому жолобі створюється суміш з рівномірно розташованим твердим, яка не змінюється і в процесі руху пульпи. Змінна об'ємна продуктивність пісків класифікатора робить рух пульпи нерівномірним. За отриманими залежностями в певні моменти часу можливо визначати середню швидкість руху і висоту пульпи у пісковому жолобі, які однозначно характеризують умови формування потоку, дають можливість відтворення механізму взаємодії між масивами матеріалу та обґрунтування шляхів підвищення точності вимірювання технологічного параметра.

The results of studying the formation and dynamics of pulp flow in the sand chute of a mechanical single-spiral classifier are presented. Upon the impact of sand and water a mixture of evenly spaced firm is formed in the sand chute that does not change during the motion of the pulp. The variable volumetric efficiency of the classifier sands makes the pulp movement uneven. The variable in time sand flow in the hydraulic system is automatically compensated by varying its height in the sand chute. Only under this condition the material balance and the continuous transporting of the material persist. There exist mathematical dependences between the variable sand costs, average speed and pulp height. Using the dependences obtained at some point in time it is possible to determine the average speed and the height of pulp in the sand chute, which characterize uniquely the conditions of formation of the flow, allow restoring the mechanism of interaction between the batches of the material and studying the ways to improve the accuracy of measurement of the process variable.
The study of the conditions of formation of pulp flow in the sand chute of a single-spiral classifier
Keywords: швидкість; висота; пісковий продукт; концентрація частинок; velocity; height